Kānsamrūat khō̜mūn kīeokap ʻāchīp sœ̄m læ ʻāchīp thānglư̄ak khō̜ng chāo ʻŪrak Lāwōi nai Čhangwat Phūket - Narumon Arunotai (Sathāban Wičhai Sangkhom Čhulālongkō̜nmahāwitthayālai, 2007)
Survey on additonal and alternative occupations for the Urak Lawoi of Phuket.